Performance Analysis of Routing Protocols for CBR Traffic in Mobile Ad-Hoc Networks - Mahmud, Md Ashek Raihan; Rahman, Md Mahbubur; Miah, Md Sipon (Journal of Information, 2016)
This paper presents the comparative performance analysis of Ad-Hoc routing protocols: Destination-sequenced distance vector (DSDV), Dynamic source routing (DSR) and Ad hoc on-demand distance vector (AODV) based on constant bit rate (CBR) traffic patterns. Simulation results show that firstly, the UDP throughput for DSR routing protocol is largest among the others. Secondly, the routing overload of DSDV and AODV is higher than DSR. Finally, DSDV shows the lowest end-to-end delay for UDP transmission than AODV and DSR.